Peningkatan Kemampuan Bahasa Anak Melalui Metode Bercerita Menggunakan Media Audio Visual di RA Raudatul Ilmi Kecamatan Medan Denai - JF, Nurul Zahriani; Rahmayani, Cut; Humaira, Humaira; Sunarti, Sunarti (Prodi PIAUD STAI Sumatera Medan, 2021)
This study aims to find out the improvement of children's language skills in R Raudhatul Ilmi. The sample in this study amounted to 32 children. Collecting data from the results of this study used techniques namely observation, question and answer, discussion and documentation. Data analysis includes related aspects carried out during the study, namely in two research cycles. The results showed that the improvement of children's language skills through storytelling methods using audio-visual media in group B in RA Raudatul Ilmi, Medan Denai District continued to increase. This can be seen from the pre-cycle data as the initial basis which is only 38% then after the action changes are increasingly visible, namely cycle I (51%) and cycle II (82.4%). Therefore, it can be concluded that the